Research on the Homogenized Postirradiation Elastoplastic Constitutive Relations for Composite Nuclear Fuels - Zhang, Jing; Zhang, Jingyu; Wang, Haoyu; Wei, Hongyang; Tang, Changbing; Lu, Chuan; Ding, Shurong; Li, Yuanming (Frontiers in Materials, 2021)
A multi-scale finite element method is developed to simulate the irradiation process and post-irradiation uniaxial tensile tests for metal-matrix composite fuels with representative volume elements (RVEs). The simulations of irradiation process are implemented under a wide range of burnup levels, with the irradiation effects on the mechanical constitutive relations of fuel particles and matrix taken into account comprehensively. The simulation results for the macroscopic post-irradiation true stress/strain curves are obtained, excluding the irradiation-induced macroscopic deformations. The effects of particle fission density, temperature and initial particle volume fraction are investigated and analyzed. The research results indicate that (1) a quasi-elastic stage appears during the post-irradiation tension, which is mainly induced by the creation of high residual compressive stresses in the particles and matrix after irradiation; (2) with the increase of effective strains, new plastic deformations increase in the particles and matrix to result in the macroscale plastic stage; (3) the macroscale irradiation softening and hardening phenomena appear, which mainly stem from the weakened deformation resistance by the irradiation-induced plastic deformations in the matrix, the enlarged particle volume fraction after irradiation, and the irradiation hardening effects of metal matrix.